2010
DOI: 10.1002/j.2051-3909.2010.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior cancer‐death events: what impact does this have on radiation therapy students?

Abstract: Purpose: In 2004, a study was undertaken to determine whether treating cancer patients affected the identity development of radiation therapy students in New Zealand. Initial data analysis revealed many students had experienced significant cancer-death events, such as family members or friends dying prior to entering the course. Methods: A further thematic analysis was undertaken of the transcript data to determine the effects of having a prior cancer-death event on students' attitudes and perceptions of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A previous small New Zealand pilot study (n = 21) found that 76% of radiation therapy students had experienced a cancer related death-event before entering undergraduate studies. 17 Several students reported that this event had infl uenced their career choice. Th e current study compares the frequency and nature of death-related events and their eff ect on attitude to life, relationships and career choice in a larger sample of radiation therapy students and a cohort of education students in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…A previous small New Zealand pilot study (n = 21) found that 76% of radiation therapy students had experienced a cancer related death-event before entering undergraduate studies. 17 Several students reported that this event had infl uenced their career choice. Th e current study compares the frequency and nature of death-related events and their eff ect on attitude to life, relationships and career choice in a larger sample of radiation therapy students and a cohort of education students in New Zealand.…”
Section: Introductionmentioning
confidence: 99%